Pengaruh Reputasi Underwriter, Kinerja Keuangan, Profitabilitas, dan Financial Leverage Terhadap Tingkat Underpricing pada Pelaksanaan Initial Public Offering (IPO) - Marcella, Angelina; Saputra , Wawan Andang (CV. Ulil Albab Corp, 2024)
The purpose of this study is to analyze several variables that influence the occurrence of IPO underpricing, such as underwriter reputation, financial performance (ROA), profitability (ROE), and financial leverage (DER). This study utilizes information obtained from the prospectus reports of companies that experienced underpricing at the time of the implementation of the IPO that have been listed on the IDX by using purposive sampling data collection methods that meet the research criteria. The research period was taken for 5 years with a total of 104 data from 253 data on issuers who carried out IPOs in 2017-2021. This study utilizes the multiple linear analysis method using secondary data types. The results of the study prove that there is a simultaneous influence between underwriter reputation, financial performance, profitability, and financial leverage of IPO underpricing levels. The reputation of the underwriter has a negative and insignificant impact on IPO underpricing, there is a significant positive relationship between financial performance on IPO underpricing, there is a significant negative relationship on profitability to IPO underpricing, and there is a negative relationship between financial leverage and IPO underpricing.